Enumeration of the Family Nyctaginaceae in India - Pramanick, Debasmita Dutta; Maiti, G. G.; Mondal, M. S. (Indian Forester, 2018)
The present article comprises the enumeration of the taxa belonging to the family Nyctaginaceae in India. In this paper, currently accepted name, basionym (if any), important synonyms, local names, phenology, distribution and ecology, uses and notes have been provided for each taxon.